Les Politiques De Preventions Et La Criminalite En Afrique Sub-Saharienne (Global Journal of Human-Social Science, 2020)
This paper aims to examine the short and long-term effects of the prevention policy on crimes in Sub-Saharan Africa over the period of time ranging from 1985-2018. We used an estimated model of panel data by the fish regression method. The results showed that an increase in government expenditures on education led to a decrease in crime in Sub-Saharan Africa. Otherwise, we also found out that the increase in defense forces led to a slight increase in the crime rate in Sub-Saharan Africa. This work has therefore shown us that the long-term prevention policy is more effective than the short-term prevention policy.
Keywords: crime; government policy; long-term prevention; short-term prevention